Therapeutic Journey and Economic Burden of Patients with Myasthenia Gravis in Italy: Results of a Real-World Analysis - Valentina Perrone; Stefania Mazzoni; Maria Cappuccilli; Margherita Andretta; Marcello Bacca; Antonietta Barbieri; Fausto Bartolini; Alessandro Chinellato; Andrea Ciaccia; Alberto Costantini; Francesco De Vita; Stefania Dell'Orco; et al. (Farmeconomia: Health Economics and Therapeutic Pathways)
AIM: This analysis investigated the population with Myasthenia Gravis (MG) in Italy, to describe epidemiology, mortality, patients’ characteristics, comorbidity profile, therapeutic management, and healthcare consumption and related costs.